Analysing dengue fever spread in Kenya using the Zero-Inflated Poisson model - Lameck Ondieki Agasa; Faith Thuita; Thomas Achia; Antony Karanja (Journal of Public Health in Africa)
Background: Dengue fever (DF), transmitted by Aedes mosquitoes, remains a major public health concern in tropical and subtropical regions. Understanding the influence of climatic variables on DF incidence is essential for improving outbreak prediction and control measures.